Metabolite/phytohormone–gene regulatory networks in soybean organs under dehydration conditions revealed by integration analysis. (3rd May 2020) - Maruyama, Kyonoshin; Urano, Kaoru; Kusano, Miyako; Sakurai, Tetsuya; Takasaki, Hironori; Kishimoto, Miho; Yoshiwara, Kyouko; Kobayashi, Makoto; Kojima, Mikiko; Sakakibara, Hitoshi; Saito, Kazuki; Shinozaki, Kazuo
Summary: Metabolites, phytohormones, and genes involved in dehydration responses/tolerance have been predicted in several plants. However, metabolite/phytohormone–gene regulatory networks in soybean organs under dehydration conditions remain unclear. Here, we analyzed the organ specificity of metabolites, phytohormones, and gene transcripts and revealed the characteristics of their regulatory networks in dehydration‐treated soybeans. Our metabolite/phytohormone analysis revealed the accumulation of raffinose, trehalose, and cis ‐zeatin (cZ) specifically in dehydration‐treated roots. In dehydration‐treated soybeans, raffinose, and trehalose might have additional roles not directly involved in protecting the photosynthetic apparatus; cZ might contribute to root elongation for water uptake from the moisture region in soil. Our integration analysis of metabolites–genes indicated that galactinol, raffinose, and trehalose levels were correlated with transcript levels for key enzymes (galactinol synthase, raffinose synthase, trehalose 6‐phosphate synthase, trehalose 6‐phosphate phosphatase) at the level of individual plants but not at the organ level under dehydration. Genes encoding these key enzymes were expressed in mainly the aerial parts of dehydration‐treated soybeans. These results suggested that raffinose and trehalose are transported from aerial plant parts to the roots in dehydration‐treated soybeans. Our integration analysis of phytohormones–genes indicated that cZ and abscisic acid (ABA) levels were correlated with transcript levels for key enzymes (cytokinin nucleoside 5′‐monophosphate phosphoribohydrolase, cytokinin oxidases/dehydrogenases, 9‐ cis ‐epoxycarotenoid dioxygenase) at the level of individual plants but not at the organ level under dehydration conditions. Therefore, processes such as ABA and cZ transport, among others, are important for the organ specificity of ABA and cZ production under dehydration conditions. Significance Statement: We analyzed the characteristics of metabolite/phytohormone–gene regulatory networks in dehydration‐treated soybean plants. Our analysis revealed the accumulation of raffinose, trehalose, and cZ specifically in dehydration‐treated roots, and our integration analysis of metabolite/phytohormone–genes indicated that several metabolite/phytohormone levels, including those of raffinose, trehalose, and cZ, were correlated with transcript levels for these key enzymes at the level of individual plants but not at the organ level under dehydration conditions.